A study on customers' attitudes towards service environment at three selected pizza hut outlets / Norhaniza Zulkaain - Zulkaain, Norhaniza (2004)
Service food is very common with service environment. Service environment is considered as part of service quality, Which emphasizes tangibles factors that is designed by service provider. Customers usually service environment as important part when evaluate service quality for particular service. As a result, we can determine attitudes that have be portray by customers encounter the service. The purpose of the study is to determine the elements that Will contribute to positive or negative customers' attitudes after trey experience particular service. This is Where the study on customers' attitudes towards service environment in food industry is significant. Customers are shown to behave their differences attitudes when experienced With different environment surroundings. Customers may compare what they seen against What they expected, if it cost them money, time, or that could have been devoted to obtaining an alternative solution. Marketers should find this study useful to recognize how customers are likely to behave towards physical surroundings. Therefore, it is true that customers shown their attitudes accordingly on what they have seen and experienced. and directly to the quality of service environment